Analysis of Lawang Sewu Museum as Dark Tourism in Semarang City - Ryan Dharmawan; Wiwik Nirmala Sari (The Postgraduate School of Tourism Sahid Polytechnic, 2026)
Lawang Sewu is one of the most iconic historical landmarks in Semarang, deeply associated with colonial heritage and tragic past events, particularly when its underground space functioned as a prison during the Japanese occupation. This historical background positions Lawang Sewu as a relevant subject within the framework of dark tourism, not merely through mystical narratives but as a medium of historical education, collective memory preservation, and humanitarian reflection. This study adopts a qualitative case study approach, employing observation, semi-structured interviews, and documentation. The analysis draws on dark tourism, cultural commodification, and phenomenology theories to illustrate how the visitor experience at Lawang Sewu extends beyond appreciating colonial architecture to engaging in historical understanding, emotional reflection, and the transformation of dark narratives into educational tourism value. The findings highlight that Lawang Sewu can be positioned as an ethical dark tourism destination that serves as a space for learning, reflection, and cultural identity reinforcement, thereby contributing positively to the development of heritage-based tourism in Semarang.